2015
DOI: 10.1007/s13142-015-0342-z
|View full text |Cite
|
Sign up to set email alerts
|

Intervention leads to improvements in the nutrient profile of snacks served in afterschool programs: a group randomized controlled trial

Abstract: Widely adopted nutrition policies for afterschool programs (ASPs) focus on serving a fruit/vegetable daily and eliminating sugar-sweetened foods/beverages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
(48 reference statements)
1
13
0
1
Order By: Relevance
“…This approach was used in order to help identify easily interpretable, actionable changes to menu planning that camps could make, as this is an approach that has been shown to be effective in other out-of-school settings. 5,23 …”
Section: Methodsmentioning
confidence: 99%
“…This approach was used in order to help identify easily interpretable, actionable changes to menu planning that camps could make, as this is an approach that has been shown to be effective in other out-of-school settings. 5,23 …”
Section: Methodsmentioning
confidence: 99%
“…This contradicts findings in other afterschool program studies. For example, Beets et al found that the adoption of healthy eating standards improved the snack type served at their sites. By design, the HEPA standards and best practices are not prescriptive, rather afterschool programs are encouraged to identify and select standards that work for their site.…”
Section: Discussionmentioning
confidence: 99%
“…A team of 2 observers performed snack observations at each site; one observer recorded for 5 random boys, and the other for 5 random girls to ensure sex equality in our samples. However, we did not look for differences by sex in the resulting data as other research in the field did not stratify by sex . The observers did not interfere with normal snack time routine while collecting data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1618 ASPs, defined as child care programs operating immediately after the school day, every day of the school year for a minimum of 2 hours, serving a minimum of 30 children of elementary age (6–12 years), operated in a school, community, or faith setting, served a snack, and were located within a 1.5-hour drive from the university of the first author, were eligible to participate. Programs were identified from a registry of ASPs operating in the state and randomly selected for invitation to participate in the study.…”
Section: Methodsmentioning
confidence: 99%